Customer-Driven Budgeting: Prepare, Engage, Execute - Talbot, Floyd (Business Expert Press, 2012)
Ebook from IG Library ; This comprehensive budgeting book emphasizes that the customer drives the business organization and processes and becomes the overriding purpose for a company's existence and success. Customer-Driven Budgeting offers a complete guide that covers every step in the budgeting cycle from the basics of organization, processes, and funding to budget execution and monitoring. It emphasizes that the budget is the starting point and catalyst for gaining customers. The budget prepares the company to supply the sales and marketing team reinforcements for giving a compelling reason for customers to buy from it.